2014
DOI: 10.1017/jse.2014.5
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Principals Towards Students With Disruptive Behaviour: An Australian Perspective

Abstract: This paper reports on the attitudes of 340 government primary principals from New South Wales, Australia, towards the inclusion of students with disruptive behaviours in schools. Principals' attitudes were examined using the Principals and Behaviour Survey (PABS), a new composite measure built upon a foundation of existing validated surveys on attitudes towards the inclusion of students with disabilities. Principal component analysis identified 3 components that were used as variables for correlations with a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Research has shown that teachers' perceptions of school inclusion vary by type of disability (de Boer et al, 2011;MacFarlane & Woolfson, 2013;Wood et al, 2014). Teachers find managing challenging behaviours one of the most difficult aspects of school inclusion (Eckstein et al, 2016;Leidig & Pössinger, 2017).…”
Section: Teachers and The Inclusive Schoolmentioning
confidence: 99%
“…Research has shown that teachers' perceptions of school inclusion vary by type of disability (de Boer et al, 2011;MacFarlane & Woolfson, 2013;Wood et al, 2014). Teachers find managing challenging behaviours one of the most difficult aspects of school inclusion (Eckstein et al, 2016;Leidig & Pössinger, 2017).…”
Section: Teachers and The Inclusive Schoolmentioning
confidence: 99%
“…To implement inclusive education, reviews stress the crucial role of strong, supportive, and distributed leadership practices that focus on developing shared visions and values (Ainscow, 2016; Ainscow et al., 2013; Billingsley et al., 2018; Cobb, 2015). Additionally, in international literature, there is extensive descriptive research on principals' subjective perspectives about inclusive education (Crockett et al., 2006; Graham & Spandagou, 2011; Irvine et al., 2010; Jahnukainen, 2015), attitudes towards inclusion (Boyle et al., 2013; Hadjikakou & Mnasonos, 2012; Porakari et al., 2015; Urton et al., 2014; Wood et al., 2014; Yan & Sin, 2015), and the relationship between leadership styles and attitudes towards inclusion (Al‐Mahdy & Emam, 2018; Hess & Zamir, 2016; Houser et al., 2011). Furthermore, findings from Hongkong (Poon‐McBrayer, 2017) show that school leaders struggled between benefits of inclusive education, autocratic decisions, and staff involvement.…”
Section: Introductionmentioning
confidence: 99%